Correlation of the modified Medical Research Council dyspnea scale with airway structure assessed by three-dimensional CT in patients with chronic obstructive pulmonary disease. (January 2019) - Yasui, Hideki; Inui, Naoki; Karayama, Masato; Mori, Kazutaka; Hozumi, Hironao; Suzuki, Yuzo; Furuhashi, Kazuki; Enomoto, Noriyuki; Fujisawa, Tomoyuki; Nakamura, Yutaro; Watanabe, Hiroshi; Suda, Takafumi
Abstract: Background: Dyspnea is a common symptom in chronic obstructive pulmonary disease (COPD). The modified Medical Research Council (mMRC) dyspnea scale is a widely used questionnaire to assess dyspnea. However, the relationship of the mMRC dyspnea scale with morphological airway structures in COPD remains unclear. We evaluated the correlation between the mMRC dyspnea scale and imaging-based airway structures in patients with COPD. Methods: The wall area (WA) and airway inner luminal area (Ai) of third-to sixth-generation bronchi and the percentage of low attenuation area with less than −950 HU (%LAA) of the lungs were measured using three-dimensional computed tomography in patients with COPD. WA and Ai were corrected by body surface area (BSA). Results: Forty-two clinically stable patients with COPD were enrolled. The median (range) mMRC dyspnea scale was 2 (0–3). The mMRC dyspnea scale score was significantly correlated with WA/BSA of fifth- and sixth-generation bronchi (Spearman correlation coefficient ρ = 0.386, p = 0.012; ρ = 0.484, p = 0.001, respectively). Partial rank correlation analysis showed that the mMRC dyspnea scale score was significantly correlated with WA/BSA of sixth-generation bronchi, independent of the confounding factors of age, body mass index, %predicted forced expiratory volume in 1 s, %LAA, and Ai/BSA (ρ = 0.481, p = 0.003). However, the %LAA and Ai/BSA were not correlated with this dyspnea scale. Conclusion: Bronchial WA assessed by three-dimensional computed tomography may be used as an assessment tool for dyspnea in patients with COPD. Highlights: Airway structures were measured using three-dimensional computed tomography (3D-CT). Dyspnea scale score was correlated with wall area of sixth-generation bronchi. Morphological airway assessment with 3D-CT is useful to assess dyspnea in COPD.